Village Elders' and Secondary School Students' Explanations of Natural Phenomena in Papua New Guinea - Pauka, S.; Treagust, David; Waldrip, Bruce (Springer-Verlag Dordrecht, 2005)
This research investigated the sources of explanations and understanding of natural phenomena in terms of the students’ cultural and school science experiences. The first phase involved interviews with eight village elders that probed their explanations and understanding of natural phenomena. The second phase involved the design, development and administration of two questionnaires on natural phenomena to 179 students in a rural boarding high school in Papua New Guinea (PNG). Most village elders gave explanations of many of the phenomena in terms of spirits, spells, magic, religion, and personal experiences. Most school-aged students choose scientific explanations of natural phenomena in terms of what they had learned in school or from personal experiences. However, many choose explanations of the same phenomena about spirits, spells and magic that came from the village, family or home. The study revealed that students’ ideas about natural phenomena are strongly governed and controlled by their school science knowledge in the school setting. It is likely that their own traditional knowledge cannot be identified in a school setting but that questionnaires in the students’ local language be given to students in their villages (as opposed to school). In addition, so as not to diminish the value of this traditional knowledge, science education programs are needed that are able to consider and harmonise traditional knowledge with school science.